Temporary intra-operative portocaval shunts, post-operative infections, and mid-term survival after cava-sparing liver transplantation - Weniger, Maximilian; Bazhin, Alexandr V. (Surgical infections, 2017)
Background: Temporary intra-operative portocaval shunts (TPCS) are believed to improve outcomes after cava-sparing liver transplantation. We hypothesize that decompression of the portal venous system via a TPCS reduces gut congestion, thereby decreasing bacterial translocation. Thus, we sought to clarify whether transplantation with a TPCS alters rates of post-operative infections and survival.Patients and Methods: Patients undergoing liver transplantation (n = 189) were stratified by usage of a TPCS and the type of intra-operative antibiotic prophylaxis. Rates of post-operative infections were analyzed using the χ2 test. The log-rank test was used to compare 120-d survival.Results: The analysis of patients transplanted with a TPCS and meropenem revealed increased infection rates with gut-specific pathogens (Escherichia coli, Escherichia faecalis, Escherichia faecium; p = 0.04) and equal 120-d survival in comparison with patients transplanted without a TPCS. When vancomycin was added to meropenem infection rates did not differ and patients transplanted with a TPCS had better survival in comparison with patients transplanted without a TPCS (p = 0.02). Within the TPCS group, the administration of meropenem and vancomycin was associated with improved survival in comparison with meropenem only (p = 0.03).Conclusion: Survival of patients may be improved by usage of a TPCS when gut-specific pathogens are covered by intra-operative antibiotic prophylaxis.